B.2 Neurologic outcome trajectory following neonatal arterial ischemic stroke (NAIS): A longitudinal observational study. (November 2021) - Slim, M; Pullenayegum, E; Aziz, A; Dlamini, N; MacGregor, D; deVeber, G; Moharir, M
Abstract : Background: Studies evaluating long-term neurologic outcomes following NAIS are scanty. We aimed to study the emergence pattern of neurologic deficits following NAIS. Methods: Neonates diagnosed with AIS were prospectively enrolled and outcomes were evaluated using the validated Pediatric Stroke Outcome Measure-Severity Classification Scheme. Neurologic outcomes were classified as normal/mild, moderate or severe. Trend analysis was conducted using Cochran-Armitage test. Results: A total of 126 neonates (59% males) were followed for a median of 5.2 years (IQR:3.4-6.4 years). The proportion of children classified as normal/mild declined from 94% to 76% >5 years post-stroke (p<0.01). Moderate and severe outcomes increased from 5% to 15% and 1% to 8% (p=0.01), respectively. Sensorimotor, language and cognitive deficits emerged in 16%, 14%, and 17% of enrolled neonates, respectively. Of those who had normal/mild outcomes at baseline, 83 remained stable throughout the study. Improvement in neurologic outcomes was seen in 8 children. Thirty-five neonates had emerging deficits at one point during follow-up. Congenital heart disease predicted the emergence of deficits (odds ratio=3.3, 95% confidence interval:1.01-10.5). Conclusions: Emerging deficits following NAIS are not uncommon and can equally manifest in sensorimotor, language or cognitive domains. Thus, long-term follow-up and close monitoring of outcomes following NAIS is crucial.